State transition probability based sensing duration optimization algorithm in cognitive radio - ZHANG Xiao; WANG Jin-long; WU Qi-hui (Tongxin xuebao)
The sensing duration to use is a trade-off between sensing performance and system efficiencies.The relation-ship between sensing duration and state transition probability was analyzed when the licensed channel stays in the idle and busy states respectively,based on which,a state transition probability prediction based sensing duration optimization algorithm was proposed.The proposed algorithm can use as little sensing duration in each frame as possible to satisfy the sensing performance constraints so as to maximize the energy and transmitting efficiencies of the cognitive networks.